IMPLEMENTASI MANAJEMEN PENDIDIKAN KARAKTER DALAM MENGEMBANGKAN MINAT SIKAP DAN PERILAKU POSITIF SISWA DI SMK N 03 KOLAKA UTARA KAB KOLAKA UTARA TP 2023/2024 - Karim (UNISAN JURNAL, 2024)
The implementation of character education programs is one of the efforts to develop students' interests, attitudes, and positive behaviors. This research aims to evaluate the implementation of character education management in developing students' interests, attitudes, and positive behaviors at SMK N 03 Kolaka Utara, Kolaka Utara District, North Kolaka. The research method used is descriptive qualitative approach. Data were obtained through observation, interviews, and documentation. The results of the study indicate that the implementation of character education management can improve students' interests, attitudes, and positive behaviors. Factors influencing the success of character education programs include the support of the school principal, teacher commitment, parental participation, selection of appropriate methods and media, and regular program evaluation. Character education programs also need to be integrated with the existing curriculum and learning activities. It is hoped that the results of this research can contribute to the development of character education programs in schools.Keywords : Management of Character Education, Interest, Attitude, and Positive Behavior